Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual Terhadap Kinerja Karyawan pada CV Polaris Surabaya - Dita Nanda Pratiwi; Handy Aribowo (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on employee performance at CV Polaris Surabaya. The research background is based on the importance of human resources as a strategic asset of the company that plays a role in planning, implementing, and controlling the achievement of organizational goals. The research method used is a quantitative approach with a correlational design. Data was collected through the distribution of questionnaires and direct observation of employee work activities. The research population includes all employees of CV Polaris Surabaya, with a sample of 100 respondents determined through the saturated sample technique. Data analysis was carried out to test the influence of each variable partially or simultaneously on employee performance. The results of the study show that intellectual intelligence, emotional intelligence, and spiritual intelligence partially have a positive and significant influence on employee performance. Simultaneously, these three variables make a significant contribution to improving individual performance in the organization. These findings indicate that the integrated development of the intellectual, emotional, and spiritual aspects of employees can be an effective strategy in improving productivity and work quality. This research provides practical implications for human resource management to design holistic employee development programs, as well as the basis for further research in the field of work psychology and organizational management.